UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA AKHLAK PESERTA DIDIK - Nur Azizah; M Mujiburrahman; Indah Nurhidayati (Al'Ulum Jurnal Pendidikan Islam, 2021)
This study aims to determine the efforts of Islamic Religious Education teachers in fostering the morals of students. This study uses a qualitative research type with the subject of class VIII students, as informants for PAI teachers, school principals, curriculum sections and counseling teachers at SMP Muhammadiyah 1 Sukoharjo. Data were taken using observation, interviews and documentation. While the data analysis by data reduction, data presentation and data verification. The results of this study are the efforts of PAI teachers in fostering the morals of class VIII students at SMP Muhammadiyah 1 Sukoharjo. Including the delivery of material, giving an example, giving advice, habituation to be kind, giving rewards and punishments. Then the supporting factors in the process of fostering the morals of students are the role of teachers, families and supporting facilities and infrastructure. Also the inhibiting factors are the different backgrounds of students, unfavorable environmental factors, habits and the influence of technology.